Efficacy of Social Media Platforms in Fostering Access to Information on Water Utility Services in Tanzania - Kafyome, Mary Hospicia; Andindilile , Michael (University of Dar es Salaam Library Journal, 2024)
This paper reports the findings of a study that investigated the efficacy of social media platforms in fostering access to information on water utility services in Tanzania particularly on Dar es Salaam Water and Sewerage Authority (DAWASA). The study specifically sought to determine the frequency at which customers access information through DAWASA’s Instagram and Facebook platforms; examine the kind of information customers access; assess the customers’ perception on the messages they access; evaluate the customers’ perception on the promptness of DAWASA’s responses to questions, comments and complaints. The study adopted a quantitative approach and specifically a descriptive research design. The study was conducted on DAWASA customers using standardised structured questionnaires which included Likert-scale questions to gather their views on interactions with the DAWASA Instagram and Facebook platforms. In all, 136 active followers of the two platforms were randomly selected and sent the questionnaires to complete and return but only 118 respondents returned their questionnaires. The Statistical Package for Service Solutions (SPSS) version 20 facilitated data analysis. The study found that most respondents accessed daily information on water allocation schedule, meter reading, bill payments and reminders, and DAWASA staff communication contacts. However, such information is not promptly responded to by DAWASA via these platforms, an anomaly that needs fixing. As such, DAWASA should optimise the use of the social media to further improve access to information by promptly responding to questions, comments, and complaints from customers on both Facebook and Instagram platforms.